Penggunaan Konstruksi Metakognitif dalam E-Modul terhadap Pembelajaran Bahasa Indonesia - Hasanah, Uswatun (Lentera: Jurnal Ilmiah Kependidikan, 2022)
Self-study awareness is an aspect that students must have in blended learning. This study discusses the effectiveness of the construction of metacognitive skills in e-modules on student achievement independently where the learning method used is blended learning. The researcher used pre-test and post-test with a control group as the quasi-experimental design used in this study. There are two classes of Indonesian language courses as the research population, and both classes are from the Sharia Faculty, UIN Raden Intan Lampung. Before collecting research data, the researcher tested the research instrument with reliability and validity tests. Meanwhile, the treatment effectiveness test can be carried out if the research data obtained has met the criteria for normality and homogeneity. However, the researcher decided to carry out the Mann-Whitney Test because the data obtained did not have a normal distribution as a prerequisite for research analysis. The findings show that there is a difference in the mean of student learning outcomes from the experimental class and the control class. This study states that there is an increase in the pretest and posttest scores of the experimental class which is greater than the control class based on the improvement in the index on the average criterion. On the other hand, the use of metacognitive construction gave a positive response to some students so that it affected the awareness of students to learn independently, and creatively, think critically, and have self-efficacy.